Logica vivente : studio sulla Logik di Christoph Sigwart - Pisano, Francesco (Studies in Neo-Kantianism, 2023)
This study of Christoph Sigwart's (1830-1904) most ambitious philosophical work focuses on a model of transcendental logic. A model that does not conform to the Kantian one because it renounces attributing universality and necessity to the laws that establish a priori the transcendental conditions of knowledge. This model entails a different meaning of "transcendental" and "a priori" free of the need for special epistemic status. Woven into the very contingency that marks the results of empirical sciences, the ensuing logic of knowledge can provide an adequate critique of the mobility of these results. The choice to explore this possibility in the form of an analysis of Sigwart's Logik (1904) is motivated by the conviction that this work, freed from the constraints of the 20th-century debate, can offer an alternative to the dismissal of the project of a transcendental epistemology. But the Logik is also an access to the lively German post-Kantian laboratory that, at the turn of the twentieth century, produced a model of scientific philosophy that profoundly influenced the following epistemological debate. Hence, this study also aims to introduce the reader to the main epistemological issues addressed by Sigwart and the Kantian tradition to which Sigwart belongs.